The Transitional Gabbroic Rocks in Bayah Geological Complex, Western part of Java, Indonesia, Inferred from XRF, ICP-MS, and Microprobe Analysis - Aton Patonah; Haryadi Permana; Ildrem Syafri (UIR PRESS, 2021)
Gabbro, is a fossil remnant of oceanic crust in western part of Java, found at Bayah Geological Complex (BGC) and Ciletuh Melange Complex (CMC), Indonesia. It has been studied by using petrographic, X-Ray Fluorescence (XRF), and inductively coupled plasma-mass spectrometry (ICP-MS) and mineralogical (microprobe) analyses. Mineral and geochemical composition of these rocks provide important clues to their origins since the rocks have been deformed and gone through auto metamorphism, beside they contain the economic mineral and or rare earth elements (REE). Gabbroic rocks in these two areas generally shows phaneritic to porphyritic texture, granular texture. These rocks in CMC are dominated by plagioclase (oligoclase to albite), hornblende, pyroxene, partly altered to tremolite, actinolite, chlorite, epidote, and sericite; meanwhile those of BGC dominantly consist of plagioclase, pyroxene, hornblende, some present of chlorite, actinolite, epidote and biotite as secondary minerals. In multi-element diagrams, gabbroic rocks in CMC show strong negative Sr and Zr, but positive Nb anomaly, while those of BGC show strong negative anomaly of Nb and Zr. In addition, based on rare earth elements (REE) diagrams, gabbroic rocks in CMC show depleted of light rare earth elements (LREE) with negative Eu anomaly, while gabbro’s in BGC show enrichment of LREE. These characteristics indicate that GBC’s and CMC’s gabbroic rocks came from different magma sources, one was formed by partial melting of depleted upper mantle reservoir while the other one was formed by partial melting of mantle wedge with active participation of subducted slab in an arc tectonic setting, suprasubduction zone which were formed at started Upper Cretaceous to Paleogene, and they had retrograde metamorphism to epidote amphibolite facies.